2012
DOI: 10.1177/1071181312561172
|View full text |Cite
|
Sign up to set email alerts
|

Not All Interruptions are Created Equal: Positive Interruptions in Healthcare

Abstract: Interruptions were studied extensively in the past but with a focus on their negative effects. Although many types of interruptions result in a break-in-task, in some cases interruptions communicate important information associated with patient's safety. The majority of previous interruption research use a reductionist approach to minimize or prevent interruptions, and minimal attention has been given to the differentiation between positive and negative interruptions. Through the analysis of relevant healthcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 40 publications
(69 reference statements)
1
40
0
1
Order By: Relevance
“…This was seen tragically in the case of Pablo Garcia, where a nurse refrained from interrupting a colleague to question an order of 38 tablets because she had learned that interruptions were undesirable in the clinical context, and therefore administered the dose (Wachter, 2015). Because interruptions are sometimes necessary for clinical work to progress (Sasangohar et al, 2012;Grundgeiger and Sanderson, 2009;Rivera-Rodriguez and Karsh, 2010;Walji et al, 2004), researchers must understand where they are inevitable and use buffer mechanisms, such as an "IV push timer" (McCurdie et al, 2014), or implement system-level interventions at the 'blunt end' to better match the needs of clinical workflow and facilitate safe and effective care.…”
Section: Mitigation Of Interruptions In Healthcarementioning
confidence: 98%
“…This was seen tragically in the case of Pablo Garcia, where a nurse refrained from interrupting a colleague to question an order of 38 tablets because she had learned that interruptions were undesirable in the clinical context, and therefore administered the dose (Wachter, 2015). Because interruptions are sometimes necessary for clinical work to progress (Sasangohar et al, 2012;Grundgeiger and Sanderson, 2009;Rivera-Rodriguez and Karsh, 2010;Walji et al, 2004), researchers must understand where they are inevitable and use buffer mechanisms, such as an "IV push timer" (McCurdie et al, 2014), or implement system-level interventions at the 'blunt end' to better match the needs of clinical workflow and facilitate safe and effective care.…”
Section: Mitigation Of Interruptions In Healthcarementioning
confidence: 98%
“…A key concern has been the potential negative impact of interruptions on the cognitive processes of the interrupted person-a natural concern from the perspective of applied cognitive psychology. Recent work has moved closer to representing the relevance of the content of interruptions for people's tasks by classifying interruptions as positive vs. negative, or necessary vs. unnecessary for the interrupted person [8,109,150]. Such classifications have emerged from the more interpretive research typical of the quality improvement and CSE research traditions, and they are needed as a first step before interventions can be considered.…”
Section: Key Questions and Perspectivesmentioning
confidence: 99%
“…Interruptions are ubiquitous and pervasive. Although some studies, in particular studies in health care contexts, have shown that interruptions can be positive (Adler & Benbunan‐Fich, 2012; Rivera & Karsh, 2010; Sasangohar, Donmez, Trbovich, & Easty, 2012), the majority of researchers agree that interruptions have a harmful effect on performance and well‐being in the workplace. Many researchers have focused on these events, and in particular on the complexity of the interrupting task (Borst, Taatgen, & van Rijn, 2015; Cades, Boehm‐Davis, Trafton, & Monk, 2007; Cades, Werner, Boehm‐Davis, Trafton, & Monk, 2008; Hodgetts & Jones, 2006; Monk, Trafton, & Boehm‐Davis, 2008; Pankok, Zahabi, Zhang, Choi, Liao, Nam, & Kaber, 2017), showing that increasing the complexity of the interrupting task increases the time needed to resume the primary task.…”
Section: Introductionmentioning
confidence: 99%